Impact of Lubricant Additives on Friction Reduction and Wear Prevention in Machinery - Amit Shishodia (International Journal of Fracture Mechanics and Damage Science, 2024)
Lubrication is essential for ensuring the lifespan and operating efficiency of machinery because it minimizes wear and reduces friction. Modern lubricants are made up of several chemical compounds called lubricant additives, which are essential to boost the lubricant's ability to reduce wear and friction. This study thoroughly examines how lubricant additives affect wear prevention and friction reduction in equipment. This work attempts to break down the principles behind the efficacy of lubricant additives and offer insights into enhancing lubrication techniques for many industrial applications using a mix of experimental analysis, tribological research, and theoretical analysis. The information provided here may be utilized to identify and formulate lubricants that are specifically suited to certain machinery and operating environments, which will eventually lead to increased productivity, dependability, and long- term viability in industrial operations.
Keywords: Lubrication; Optimization; friction reduction; industrial applications; lubricant additives; machinery; tribology; wear prevention